Ultimate strength of container ships subjected to combined hogging moment and bottom local loads, Part 2: An extension of Smith's method. (May 2020) - Tatsumi, Akira; Htoo Ko, Han Htoo; Fujikubo, Masahiko
Abstract: This paper is the second of two companion papers concerning the ultimate hull girder strength of container ships subjected to combined hogging moment and bottom local loads. The nonlinear finite element analysis in Part 1 has shown that local bending deformation of a double bottom due to bottom lateral loads significantly decreases the ultimate hogging strength of container ships. In this Part 2, extending Smith's method for pure bending collapse analysis of a ship's hull girder, a simplified method of progressive collapse analysis of ultimate hogging strength of container ships considering bottom local loads is developed. The double bottom is idealized as a plane grillage and the rest part of the cross section as a prismatic beam. An average stress-average strain relationship of plate/stiffened plate elements employed in Smith's method is transformed into an average stress-average plastic strain relationship, and implemented in the conventional beam finite element as a pseudo strain hardening/softening behaviors. The extended Smith's method is validated through a comparison with nonlinear finite element analysis. Highlights: Double bottom bending due to local loads accelerates buckling and yielding of stiffened panels in outer bottoms. After the outer bottom collapses, the inner bottom does not effectively work as a strength member against hogging moment. An extended Smith's method which can consider the effects of the bottom local loads is proposed. The double bottom is idealized as a plane grillage and the side structure as a prismatic beam in the proposed method. Estimation of the extended Smith's method has a good agreement with that of shell FEM.